Problematic internet use and related factors in patients with opioid use disorder - Bal, Neşe Burcu; Yeşil Örnek, Bahar (Journal of Dependence, 2024)
Objective: Problematic internet use constitutes a critical public health issue. People with problematic internet use have a significantly higher risk of abusing various substances. The aim of this study was to determine the level of problematic internet use in people diagnosed with opioid use disorder and to examine the relationship between opioid use disorder and problematic internet use in terms of individual and clinical variables. Method: Sociodemographic questionnaire and Young Internet Addiction Test (YIBT) were administered to patients with opioid use disorder. Patients who scored ≥50 points on the YIBT were considered to have problematic internet use. Results: The prevalence of problematic internet use was 24.4%, while the prevalence of internet addiction was 1.4%. Patients with problematic internet use had higher unemployment rates and lower monthly income levels than those without problematic internet use. Conclusion: The results of the study suggest that problematic internet use may perpetuate or chronicize opioid use disorder. Adding preventive interventions and assessing opioid users for problematic internet use may contribute to the treatment of opioid use disorder.